2013
DOI: 10.1155/2013/603913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ivabradine on Endothelial Function in Diastolic and Right Heart Failure Patients

Abstract: Background. Ivabradine is an If ion current inhibitor that has proved to reduce mortality in patients with systolic heart failure by slowing heart rate without decreasing myocardial contractility. Photoplethysmography is a simple, low-cost optical technique that can evaluate vascular function and detect changes in blood flow, pulse, and swelling of tissular microvascular space. Objective. To evaluate the effect of ivabradine on endothelial function by photoplethysmography in diastolic and right heart failure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…One of the controversial candidates for the treatment of ED is the if-channel inhibitor ivabradine. A number of studies have revealed its positive effect on both endothelium-dependent vasodilation and eNOS expression in both animals and humans (Bolduc et al 2011;Musikhina et al 2012;Orea-Tejeda et al 2013). However, the authors of some studies note that there was no significant improvement in vasodilation under the action of ivabradine in patients with microvascular angina (Villano et al 2013), as well as in patients with other forms of coronary heart disease (Jochmann et al 2014) or type II diabetes (Nerla et al 2012).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…One of the controversial candidates for the treatment of ED is the if-channel inhibitor ivabradine. A number of studies have revealed its positive effect on both endothelium-dependent vasodilation and eNOS expression in both animals and humans (Bolduc et al 2011;Musikhina et al 2012;Orea-Tejeda et al 2013). However, the authors of some studies note that there was no significant improvement in vasodilation under the action of ivabradine in patients with microvascular angina (Villano et al 2013), as well as in patients with other forms of coronary heart disease (Jochmann et al 2014) or type II diabetes (Nerla et al 2012).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…A "stressz hypokalaemia" is ß 2 -receptor stimuláció által mediált folyamat (a K + -transzport a sejtbe extracelluláris hypokalaemiát eredményez). (29,30,31).…”
Section: Moser Györgyunclassified
“…Other new treatment options for improving endothelial function are also being researched currently. These include the eNOS transcription enhancer AVE3085, Ivabradine and Sphingosine-1-phosphate amongst others [41][42][43].…”
Section: Improving Endothelial Function In Diabetesmentioning
confidence: 99%